2010
DOI: 10.3109/03009742.2010.517214
|View full text |Cite
|
Sign up to set email alerts
|

Making the rheumatologist aware of patients' non-adherence does not improve medication adherence in patients with rheumatoid arthritis

Abstract: Supplying the rheumatologist a report with information about medication use and adherence did not change adherence or patients' beliefs about medication. Further research is necessary to ensure effective support for adherence for individual patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…The description of interventions ranged from ‘one-on-one instruction’,25 ‘group education’,26 ‘telephone-based pharmacy advisory’,27 to ‘text message reminders’ 28. Fourteen of 23 interventions were designed to directly target medication adherence, with all but one intervention29 directed at patients with rheumatology. This exception was an instrument providing rheumatologists with structured information about their patients’ non-adherence, which was not shown to have an impact on adherence or disease-related outcomes 29…”
Section: Resultsmentioning
confidence: 99%
“…The description of interventions ranged from ‘one-on-one instruction’,25 ‘group education’,26 ‘telephone-based pharmacy advisory’,27 to ‘text message reminders’ 28. Fourteen of 23 interventions were designed to directly target medication adherence, with all but one intervention29 directed at patients with rheumatology. This exception was an instrument providing rheumatologists with structured information about their patients’ non-adherence, which was not shown to have an impact on adherence or disease-related outcomes 29…”
Section: Resultsmentioning
confidence: 99%
“…One study 59 did not find that targeting beliefs about medication had any effect on DMARD adherence. Another study 60 found that supplying a nonadherent patient's rheumatologist with a report about medication use and adherence did not change adherence or the patient's beliefs about medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Both adherence intervention programs were intensive, with inconsistent results and limited effect at best. Finally, our group demonstrated that supplying written information about patients' nonadherence and adherence to the rheumatologist was insufficient to increase patients' adherence on drug therapy [76].…”
Section: Interventions In Ramentioning
confidence: 94%
“…Although education about medication and medication use, as well as self-management Review interventions, are often part of the treatment in RA, adherence is seldom reported as an outcome measure in studies into the effect of these interventions [73]. Only three studies assessed the effect of a medication adherence intervention in RA using adherence as an outcome measure [74][75][76]. One study demonstrated an improvement in adherence to d-penicillamine following a patient education program, including seven one-to-one visits of 30 min each [14].…”
Section: Interventions In Ramentioning
confidence: 99%